PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Digdowiseiso, Kumba; Bambang Subiyanto; Reza Dwi Cahyanto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the effects of Local Own-Source Revenue, Balancing Fund, and Capital Expenditure on Financial Performance of Regency and City Governments in Central Java Province over the period 2015-2019. The population in this study were all regencies and cities in Central Java Province. The results of the study indicate that both Local Own-Source Revenue and Capital Expenditure have a positive and significant effect on the Financial Performance of Regency and City Governments in Central Java Province. Meanwhile, the Balancing Fund has a negative and significant effect on the Financial Performance of Regency and City Governments in Central Java Province.